(Dis)connected - Savory, Alita, author; Levy, E. J., advisor; Thompson, Deborah, committee member; Little, Ann, committee member (Colorado State University. Libraries, 2014)
I have been interested in learning about alternative lifestyles for years. This may be because I've known so many miserable people trapped within serial-monogamous lifestyles, and I wanted to break away from this chain of misery. For a long time, I thought that all I was interested in was sex. I read books about prostitution in the west, took a class about the history of sexuality in America, and wrote about my own experiences with sex and BDSM for writing workshops. Due to these interests, I thought what I wanted to write about was BDSM and how practitioners of this lifestyle use power in extraordinary and transparent ways within their relationships. I realized as I wrote that I was fascinated less with the sexual aspects of relationships and more with the ways that people were able to find love and sustain romantic relationships. This thesis began as an idea to explore sexual relationships, but it has transformed into something much more powerful: a memoir about the search for connection.